Purchase Intention of Grooming Products: The Value-Attitude-Behaviour (VAB) Model - Andy Wijaya; Erbin Chandra; Julyanthry Julyanthry; Vivi Candra; Salmon Martua Simarmata (International Journal of Entrepreneurship and Sustainability Studies, 2021)
Grooming products are now one of the daily necessities needed in human life. Not only women who use grooming products, but the majority of men also need grooming products to improve their appearance. The urgency of this research is to explore the values ??that influence the attitudes of men in Indonesia towards grooming products and their intention to purchase these grooming products, using the Value-Attitude-Behaviour (VAB) model. The research instrument used a questionnaire that was distributed online via WhatsApp and Telegram groups during June-July 2021, which resulted in 111 responses. Hypothesis testing was carried out using a variant-based Structural Equation Modeling (SEM) called Partial Least Square (PLS) and the SmartPLS application version 3.0 as a tool to analyze it. The results showed that self-concept (self-image and self-consciousness) and product involvement had a positive and significant effect on men's attitudes towards grooming products and their intention to purchase these products. Furthermore, the effect of men's attitudes towards grooming products on their intention to purchase products also obtained significant result. The results of this study illustrate that self-concept and product involvement have an important role in determining men's attitudes towards grooming products, which in turn will have an impact on their intention to purchase care products to improve their appearance. For further research, it is better to increase the number of samples that are able to represent the entire population and also refer to other factors that influence the purchase intention of grooming products and the use of other approaches in predicting purchase intention such as the TRA model. This study is expected to contribute to the development of male grooming product industry in the country by providing an overview to marketers about the important role of self-concept and product involvement in determining men's attitudes towards grooming products, which in turn will have an impact on their intention to purchase these products to improve their appearance.